1981
DOI: 10.1093/ajcn/34.12.2734
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids in humans fed diets containing beef or fish and poultry

Abstract: One half of a group of 129 men and women (74 men and 55 women), in a cross-over design at, within a self-selected diet, one egg and at least 5 oz of beef daily for 3 months while the other half at one egg and at least 5 oz of poultry and fish daily. Then they reversed their diets for 3 months. Blood samples were drawn by venipuncture before the study started and at the end of the 3 and 6 months, for analyses of serum total cholesterol, triglycerides, and high density lipoprotein cholesterol. No statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Fat as a proportion of food energy has only decreased from 42.3 to 41.3 and the proportion of fat consumed as meat or meat products has hardly changed. Animal fats are perceived to be bad by the public because of the historical view that eating cholesterol was a major risk factor for CHD, but there have been few effective studies of the specific effect of eating meat on the concentration of plasma cholesterol; Flynn et al 49 ,50 compared diets containing 5 oz of beef, fish or chicken and observed no significant differences in plasma cholesterol for the three diets. This is perhaps not unexpected since a dietary change of this magnitude would have little effect on the total or saturated fatty acid intake, and equally any change in polyunsaturated fatty acids would not only be small, but they are less effective in lowering plasma cholesterol than are the saturated fatty acids in increasing it.…”
Section: Fat Consumptionmentioning
confidence: 99%
“…Fat as a proportion of food energy has only decreased from 42.3 to 41.3 and the proportion of fat consumed as meat or meat products has hardly changed. Animal fats are perceived to be bad by the public because of the historical view that eating cholesterol was a major risk factor for CHD, but there have been few effective studies of the specific effect of eating meat on the concentration of plasma cholesterol; Flynn et al 49 ,50 compared diets containing 5 oz of beef, fish or chicken and observed no significant differences in plasma cholesterol for the three diets. This is perhaps not unexpected since a dietary change of this magnitude would have little effect on the total or saturated fatty acid intake, and equally any change in polyunsaturated fatty acids would not only be small, but they are less effective in lowering plasma cholesterol than are the saturated fatty acids in increasing it.…”
Section: Fat Consumptionmentioning
confidence: 99%
“…The cholesterol associated with the soluble HDL was then measured enzymatically. The ef fect of freezing on HDL was considered negligible from data in our laboratory [23] and from data reported by some [43], but not by others [44], who reported that mean HDL-C was 2 mg/dl higher in frozen compared to fresh samples.…”
Section: Collection Of Blood and Analysesmentioning
confidence: 57%
“…All had been in our longitudinal study of aging for 18 years and had previously volunteered to be in past feed ing studies during which they kept records of daily food intake [11][12][13]23,24]. The hypercholesterolemics used diet therapy only.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of these changes have not shown evidence of their efficacy [13,27]. One of the main reasons for this is that they have frequently been introduced simultaneously so that the individual effect of each modification could not be distinguished.…”
mentioning
confidence: 99%